PERAN PENDIDIK AGAMA ISLAM TERHADAP PEMBENTUKAN KEPRIBADIAN ANAK USIA DINI - Tri Andiyanto (Institut Agama Islam Negeri Metro, 2021)
The role of educators in the formation of early childhood personalities in realizing learning situations and the learning process to achieve the goals of national education optimally in developing people who believe and fear God Almighty, have noble character, are healthy, knowledgeable, intelligent, creative, independent, and become citizens who are democratic and responsible, and have competitiveness at the international level. Because with education it will form a nation that is more civilized and has noble character. Islamic education is as a preparation for cadres with good character in order to build a world empire that is prosperous, dynamic, harmonious and sustainable as indicated by Allah. Thus Islamic education should be the most ideal education, because we only have a full and multi-dimensional insight into life.